EVALUATION OF MEDIUM VOLTAGE PROTECTION NETWORK 20 KV IN PLTD MERAWANG BANGKA - Juara Mangapul Tambunan; Albert Gifson; Harry Saputra (Sutet, 2016)
Medium voltage feeder is a media for distribute power electric from main stasion to the customer. But in the fact, the feeders almost have a disturbance, such as short circuit disturbance. So is needed protection system which is fulfill the qualification such as sensitivity, realibilty, and speed, which all of that depend on the accuration of tool protection setting. In general it used for medium voltage feeder are Over Current Relay (OCR) and Ground Fault Relay (GFR), that is relay which has function to instruction the PMT for open the circuit, so SUTM/SKTM which has disturbance separate from nerwork. In this final project it will discuss about condition in the protection system for medium voltage 20 KV network in PLTD Merawang Bangka.